Submandibular Gland Pathogenesis Following SARS-CoV-2 Infection and Implications for Xerostomia - Sasso-Cerri, Estela [UNESP]; Martinelli, Vitor Dallacqua [UNESP]; de Oliveira, Salmo Azambuja; da Silva, André Acácio Souza; de Moraes, Juliana Cerini Grassi [UNESP]; Cerri, Paulo Sérgio [UNESP] (MDPI, 2024)
Although SARS-CoV-2 induces mucin hypersecretion in the respiratory tract, hyposalivation/xerostomia has been reported by COVID-19 patients. We evaluate the submandibular gland (SMGs) pathogenesis in SARS-CoV-2-infected K18-hACE2 mice, focusing on the impact of infection on the mucin production and structural integrity of acini, ductal system, myoepithelial cells (MECs) and telocytes. The spike protein, the nucleocapsid protein, hACE2, actin, EGF, TNF-α and IL-1β were detected by immunofluorescence, and the Egfr and Muc5b expression was evaluated. In the infected animals, significant acinar hypertrophy was observed in contrast to ductal atrophy. Nucleocapsid proteins and/or viral particles were detected in the SMG cells, mainly in the nuclear membrane-derived vesicles, confirming the nuclear role in the viral formation. The acinar cells showed intense TNF-α and IL-1β immunoexpression, and the EGF-EGFR signaling increased, together with Muc5b upregulation. This finding explains mucin hypersecretion and acinar hypertrophy, which compress the ducts. Dying MECs and actin reduction were also observed, indicating failure of contraction and acinar support, favoring acinar hypertrophy. Viral assembly was found in the dying telocytes, pointing to these intercommunicating cells as viral transmitters in SMGs. Therefore, EGF-EGFR-induced mucin hypersecretion was triggered by SARS-CoV-2 in acinar cells, likely mediated by cytokines. The damage to telocytes and MECs may have favored the acinar hypertrophy, leading to ductal obstruction, explaining xerostomia in COVID-19 patients. Thus, acinar cells, telocytes and MECs may be viral targets, which favor replication and cell-to-cell viral transmission in the SMG, corroborating the high viral load in saliva of infected individuals.
Keywords: acinar cell; DMV; immunofluorescence; mucin; myoepithelial cell; salivary gland; sialadenosis; Sjögren’s syndrome; telocytes; transmission electron microscopy